Immunofluorescent Antibody Test (IFAT) for Trypanosoma cruzi in dogs from urban and rural areas of Pelotas, RS - Charlene Nascimento dos Santos (Boletim de Indústria Animal, 2015)
Chagas disease (CD) is a zoonosis with the protozoan Trypanosoma cruzi as the causative agent. Dogs are considered the main domestic reservoir for T. cruzi in most Latin American countries and in some areas of the United States. In southern Brazil, despite being an endemic area of the disease, the prevalence in dogs is still unknown. This study aimed to evaluate the frequency of T. cruzi antibodies in dogs from urban and rural areas of Pelotas, RS, Brazil. A total of 227 canine sera were used for serological tests, of which 99 were from urban areas and 128 were from rural areas of Pelotas. Information regarding the environment and the possible risk factors (origin, rural contact, age, breed, confinement and gender) to which the dogs were exposed were recorded. Indirect immunofluorescence was used to assess the presence of specific immunoglobulins (IgG) anti-T. cruzi in the serum of dogs. Of the 227 sera analyzed, 81 (35.7%) exhibited anti-T. cruzi, which represented 34.3% of the dogs from the urban area and 36.7% of the dogs from the rural area. Among the variables analyzed, rural contact and male gender showed an association with seropositivity for T. cruzi. The detection of T. cruzi antibodies in the serum of these dogs emphasizes the need to study trypanosomiasis in this important domestic reservoir of Chagas disease.